Palladium(II) Acetate Mediated Dimerization/Cycloisomerization of 2-Sulfonyl-4-alkynones: Synthesis of trans-1,2-Difurylethylenes - Chang, Meng-Yang; Lai, Kai-Xiang (Synthesis, 2019)
This paper describes a one-pot, atom-economic, easy-operation, open-atmosphere method for the synthesis of trans-1,2-difurylethylenes by the straightforward Pd(OAc)2-mediated dimerization/cycloisomerization of 2-sulfonyl-4-alkynones in the presence of Na2CO3 and PPh3 under refluxing EtOH conditions, and proposes and discusses a plausible mechanism. This protocol provides a highly effective annulation via two carbon–oxygen (C–O) single-bond and one carbon–carbon (C=C) double-bond formations.
Keywords: palladium(II) acetate; dimerization/cycloisomerization; 4-alkynones; 1,2-difurylethylenes; one-pot atom-economic method